HUMANIZATION IN MULTIPROFESSIONAL CARE IN THE INTENSIVE CARE UNIT - Evelly da Silva Olanda, Debora; Gnecco de Almeida, Adriana; Lucena da Silva, Amanda; Thallyta Alexandre de Pontes, Arunna; da Silva Carvalho, Denise; de Oliveira Souza, Eclesia; Gomes do Nascimento, Evelyn; Junio do Nascimento, Francisco; Alexandre Judeikis, Guilherme; Santos Sousa, Kallyany; Feitosa Rodrigues, Lutigard; Casado de Freitas Silva, Rosany; et al. (Health and Society, 2022)
The Intensive Care Units (ICU) were developed to provide assistance to people in critical condition, being reformulated by the National Humanization Policy (PNH), also called HumanizaSUS, reorganizing health care practices, in order to consider the uniqueness, the multidimensionality and the social context of the patient and his family. Being a humanization defined as a set of actions to qualify a complete assistance, valuing care as the main basis. This study aimed to analyze the scientific contributions on the humanization of care in the Intensive Care Unit, during the period from 2000 to 2012. This is an integrative review of the literature, which allows the realization of scientific knowledge, based on previous studies conducted. Online searches were performed at the Virtual Health Library, Scielo (Scientific Electronic Library Online) and LILACS (Latin American Literature). Counting with 10 productions, analyzed with an instrument created by the researcher herself. The results showed that the humanization of care contributes significantly to the recovery of the patient in the Intensive Care Unit. However, there are difficulties to overcome, related to issues of the patient and his / her family, the nursing team and health institutions. There is a need for training and awareness of professionals to improve care for critically ill patients.